Effects of Dietary Vitamin E and Selenium on Aspartate Aminotransferase and Alanine Aminotransferase Activities in Rats Treated with High Doses of Glucocorticoid - Erisir, Mine; Beytut, Ebru; Kandemir, Fatih Mehmet; Benzer, Fulya (Medwell Online, 2009)
The effects of dietary intake of vitamin E and selenium on aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities in rats treated with high doses of prednisolone were investigated: Rats were divided into 5 groups. Groups 3, 4 and 5 received a daily supplement in their drinking water of 20 mg vitamin E, 0.3 mg Se and a combination of vitamin E and Se, respectively, for 30 days. For 3 days subsequently, the control group (group 1) was given a placebo and the remaining 4 groups were injected intramuscularly with 100 mg kg(-1) body weight prednisolone. After the last administration of prednisolone, 10 rats from each group were killed at 4, 8, 12, 24 and 48 h and the activities of aspartate aminotransferase and alanine aminotransferase enzymes in their tissues were measured. In the group, treated with prednisolone alone, AST activity in the liver was not affected, the ALT activity was significantly decreased at 12 h only. AST and ALT activities in the kidneys were significantly decreased by prednisolone at all time periods. AST activity in the heart also decreased in the prednisolone group between 4 and 24 h, significantly at 12 h. Significant decreases were found at 4, 8 and 12 h in the heart ALT activity of the prednisolone administered group. AST activity in the liver, kidneys and heart was lower in vitamin E and Se supplemented groups than control and prednisolone groups. In the combination group, compared to both the control and prednisolone groups, AST activity in the kidneys and heart was decreased, but increased in liver. Vitamin E and Se alone or in combination had a preventive effect on the decrease of ALT activity in the liver and kidneys caused by prednisolone. ALT activity in the heart tissue of the vitamin E supplemented group was found to be increased at all time periods, however, it reduced in the Se and combination groups compared to the prednisolone group. Therefore, the present study demonstrates that vitamin E and Se alone or in combination may prevent the decrease in ALT activity in the liver and kidneys caused by high doses of prednisolone.
Keywords: Glucocorticoid; aspartate aminotransferase; alanine aminotransferase; vitamin E; selenium